Pengaruh Kepuasan Kerja dan Beban Kerja Terhadap Kinerja Karyawan pada CV Karya Taruna Teknik Depok Jawa Barat - Wisnugroho Aji; Sheila Ardilla Yughi (Departement of Mathematics Education, 2024)
This research aims to find out the impact of job satisfaction and workload on employee performance on CV. The research method used is a quantitative method with a sample of 85 respondents. Based on the results of the research on the first hypothesis obtained t count value > t table or (6,749 > 1,98896) It is also reinforced with the value of Sig. < 0,05 or (0,000 < 0,05) so that partially variable Job satisfaction there is a significant influence on Employee Performance on the CV. The work of Taruna Technical Depok Java West. On the test results on the second hypotheses obtains a value of t count > t Table or (7,899 > 1, 98896) This is also strengthened with a Sig. value < 0.05 or (0.000< 0,05). Thus partially the workload variable has a significant impact on the performance of Employees on CV.